Nonfunctioning Pituitary Adenoma That Changed to a Functional Gonadotropinoma - Gerson Geovany Andino-Ríos; Lesly Portocarrero-Ortiz; Carlos Rojas-Guerrero; Alejandro Terrones-Lozano; Alma Ortiz-Plata; Alfredo Adolfo Reza-Albarrán (Case Reports in Endocrinology)
Objective. Pituitary adenomas can be classified as clinically functional or silent. Depending on the reviewed literature, these are the first or second place in frequency of the total pituitary adenomas. Even rarer is the presence of a functional gonadotropinoma since only very few case reports exist to date. The conversion of a clinically silent to functional pituitary adenoma is extraordinarily rare; the mechanisms that explain these phenomena are unknown or not fully understood. Methods. We report the case of a woman who initially had a nonfunctional gonadotropinoma and in the course of her medical condition showed biochemical changes in her hormonal pituitary profile compatible with a functional gonadotropinoma. Results. We considered that the patient had a functional gonadotropinoma due to the hyperestrogenemia in the context of secondary amenorrhea, resolving the hyperestrogenemia after almost complete resection of the tumor. Conclusion. It is necessary to point out from a clinical and/or biochemical point of view the change in functionality that a nonfunctional pituitary adenoma may have. In the case of our patient, the suspicion of this change in functionality became evident when we found an increase in the FSH/LH ratio and a progressive increase in serum estradiol concentrations when the patient had amenorrhea.